Identification of Anti-Inflammatory Components from Launaea sarmentosa Using In Vitro Cell Model - Nguyen, Thanh Quoc Chau; Vo, Khang Thanh; Duong, Cua Dinh; Huynh, Toan Phu; Ca, Lieu Thi Thuy; Dang, Giao Huynh (Indonesian Journal of Chemistry, 2025)
Launaea sarmentosa (Willd.) Kuntze, a medicinal herb known for treating inflammatory diseases, was examined for its anti-inflammatory compounds to identify novel therapies. This study indicated that hexane and ethyl acetate fractional extracts significantly reduced NO secretion in LPS-stimulated RAW264.7 macrophages, indicating the presence of potential anti-inflammatory compounds. Additionally, four anti-inflammatory compounds, including taraxasteryl acetate (1), esculetin (2), pyrimidine-2,4-dione (3), and 5-hydroxypryrolidin-2-one (4), were isolated, and their structures were characterized using 1D and 2D-NMR. This study marked the first report of taraxasteryl acetate, pyrimidine-2,4-dione, and 5-hydroxypryrolidin-2-one being isolated from this species. Furthermore, these compounds exerted their anti-inflammatory role by inhibiting NO production and TNF-α expression. Thus, this study contributes to identifying anti-inflammatory constituents from L. sarmentosa and highlights a potential approach for developing phytotherapeutic agents.